111 Evaluation of Dietary Mycotoxin Control Strategies on Nursery Pig Growth Performance and Blood Measures. (12th April 2022) - Becker, Larissa L; Gebhardt, Jordan T; DeRouchey, Joel M; Woodworth, Jason C; Tokach, Mike D; Goodband, Robert D; Vidal, Arnau; Gougoulia, Christos
Abstract: A total of 4, 318 pigs (337×1050, PIC; initially 6.5±0.08kg) were used in a 35-d trial to evaluate dietary mycotoxin control strategies on nursery pig performance and blood measures. Pigs were weaned at 21-d of age and randomly allotted to 1 of 5 dietary treatments. A total of 160 pens were used with 80 double-sided 5-hole stainless steel fence line feeders, with feeder serving as the experimental unit. For each feeder, 1 pen contained 27 gilts and 1 pen contained 27 barrows. There were 16 replications/treatment. A common phase 1 diet was fed in pelleted form for 7-d prior to treatment diets. Experimental treatments were fed from d 7 to 42 after weaning (d0 to 35 of study) and included a low deoxynivalenol (DON) diet (1.12±0.623 mg/kg), high DON diet (2.34±1.809 mg/kg), high DON+ sodium metabisulfite (SMB), high DON+ 1 of 2 mitigating products; Technology1, or Technology1+. Technology1 and 1+ are comprised of clays, yeast cell wall components and a blend of plant extracts. Technology1+ also contains SMB. Overall (d0 to 35), pigs fed high DON had decreased ( P < 0.05) final BW, ADG, and ADFI compared with low DON. Additionally, pigs fed high DON+SMB had increased (P<0.05) ADG compared with all other treatments. An increase ( P < 0.05) in G:F was observed in pigs fed high DON+SMB or high DON+Technology1+ compared with low DON or high DON+Technology1 with high DON intermediate. Analysis of dried blood spots collected on d 35 revealed pigs fed high DON or high DON+Technology1 had increased ( P < 0.05) DON concentrations compared with low DON with high DON+SMB and high DON+Technology1+ intermediate. In summary, pigs fed high DON had reduced performance compared with low DON. Sodium metabisulfite supplementation to high DON led to ADG and G:F that exceeded low DON, whereas Technology1+ resulted in similar ADG and improved G:F compared with low DON.